Self-regulation of insect communities in agrocenoses of organic farming systems - Sabluk, V.; Zapolska, N.; Shendryk, K.; Dimitrov , V. (Quarantine and plant protection, 2023)
Goal. Establishing the effect of organic farming on the preservation of useful entomofauna in agrocenoses of winter wheat and sugar beet and determining its role in controlling the number of phytophages. Methods. Field, laboratory and statistical. Results. It was found that organic farming system, which excludes the use of chemicals in crop cultivation technologies, contributes to the accumulation of useful entomofauna in agrocenoses, which significantly affects the population density of certain phytophagous species due to predation and parasitism as major causes. In particular, the number of Carabidae, coccinellids, goldeneyes and syrphids is several times higher compared to industrial farming system. Thus, according to our experimental data, the population density of these entomophages in the agrocenoses of winter wheat and sugar beet in organic farming was 4−5 times higher than in industrial one. Accordingly, the number of weevils, aphids and other phytophages in these crops in organic farming was 3−4 times fewer than in industrial one. The population density (per 1 m2) of weevils in sugar beet grown in organic system was 3.0, while in industrial one it was 5 times higher (15). The same may be stated about aphids, Anisoplia austriaca, Heteroptera, etc. Conclusions. In organic cropping system, the population density of beneficial entomofauna in sugar beet and winter wheat agrocenoses was 4−5 times higher than in industrial cropping system, what to a certain extend affected the population density of pests.